La performatividad de género según La hija extranjera o el compromiso político de Najat El Hachmi - Moszczyńska-Dürst, Katarzyna (Studia Romanica Posnaniensia, 2020)
The objective of this article consists in analysing how and to what extent “the psychic life of power” (Butler, 2001) and the “synchronicity of the non-synchronic” (Cros, 2002) organise discourse practices of the hybrid identity (Sabaté, 2014) encoded in Najat El Hachmi’s La hija extranjera (2015), a novel written from a marked transcultural and feminist perspective. The protagonist and narrator in first person, a young Catalan woman of Moroccan origin (“the foreign daughter” of the title), is torn between contradictory ideologies, hopes and desires. She is suspended between the Spanish and the Moroccan cultures, between submission and rebellion. Likewise, we will see how the narrator reveals the great political potential of literature that lies in “resignification” (Butler, 2002).